The Hype of Coronavirus Pandemic in Southeast Nigeria: Some Thoughts - Isiani, Mathias Chukwudi; Obi-Ani, Ngozika Anthonia; Obi-Ani, Paul (South Asian Journal of Social Sciences and Humanities, 2021)
The escalation of the Coronavirus to other countries around the world prompted WHO to declare  the virus on January 30, 2020 a public health emergency (WHO, 2020). In lieu of its quick  spread and high mortality rate, the WHO termed the virus a pandemic. However, in Nigeria,  efforts to contain and sensitize the populace about this pandemic were put in place, media  platforms were copiously engaged by the Nigeria Centre for Disease Control (NCDC), sensitizing the masses on the preventive measures against the coronavirus. Despite their efforts,  some social media users inundated the people with fake news, ‘end-time’ religious teachings, rumors and misinformation about 5G ultra-waves. The dominant questions are: what roles did  the different social media platforms play in information dissemination on Covid-19 in Southeast  Nigeria? What were peoples’ reactions to these messages? How do the people view messages  from government viz-a-viz their religious leaders or other sources? Why do individuals deem it  necessary to ‘forward’ such messages to relatives, friends and different social media platforms  like WhatsApp and Facebook? In answering these questions, this qualitative study explores social media outlets such as Facebook, Twitter, WhatsApp, blogs, online newspapers and YouTube where the contestations about the pandemic are most pronounced. This study through  its finding using statistical frequencies, demonstrates that before the detection of the first victim  of Covid-19 in Nigeria, the region was already agog with social media (mis)information about  the pandemic causing panic among the populace followed by the frenzy need to ‘forward’ such  messages to those in their contacts. In lieu of this, this study examines these contestations and  contradictions about Covid-19 in Southeast Nigeria.
Keywords: Covid-19; Nigeria; Social Media; News; Southeast